Development Of An Electric Motorcycle Trainer Kit As A Learning Medium For Electrical Engineering And Automotive Engineering Majors In Vocational High Schools - Supraptono, Eko; Wibowo, Apriansyah; Wijaya, M. Burhan Rubai; Rohman, Shohihatur; Siraj, Ubaidillah; Qunefi, Fuat; Mubarak, Raihan Fa’iq; Baskoro, Aldo Luhung; Aryaditama, Geofan; Fathimah, Aisya Fathimah (Jurnal Abdimas, 2025)
The increasing demand for electric vehicles (EVs) due to global warming and environmental issues necessitates specialized knowledge in this field. This research develops an electric motorcycle trainer kit designed to enhance learning in vocational high schools, specifically in the Electrical Engineering and Automotive departments. The research aimed to design and validate a trainer kit that accurately represents an electric motorcycle's electrical system, facilitating hands-on learning for students. The methodology involved data collection, product design, and implementation with validation by field experts. Results showed that the trainer kit significantly improved students' understanding and practical skills related to electric vehicle systems. In conclusion, the electric motorcycle trainer kit proved to be an effective educational tool, supporting the development of competencies required for the growing electric vehicle industry. Further improvements in the aesthetic and technical aspects of the kit could enhance its future applications.